Ludic Taunting: Does Taunting Work Differently in Video Games? - SF Luthfie Arguby Purnomo; SF. Lukfianka Sanjaya Purnama; Lilik Untari; Agung Prasetyo Wibowo; Nabil Aqib; Yosse Vira Oktaviana (Universitas Sanata Dharma, 2022)
Studies on taunting in video game context tend to mull over around how players taunt other players via online chat features. Studies on how taunting works in games with in-game taunt features are under investigated. Examining twenty-seven gamestory-wise and gameplay-wise games, we argue, through this sociolinguistic study, that taunting designed for game characters is better termed ludic taunting since it has different functions from that of taunting in games with online chat feature and in real life. Ludic taunting has two major functions namely narrative and mechanical. The former which refers to taunting for game story-bound purposes is classified into archetyping, cameoing, and mythopoesing. The latter, for game play-bound purposes, is classified into buffing, cosmeticizing, cueing, debuffing, hinting, and rewarding. Game designers and scholars could employ this study as a reference in designing games with in-game taunt features.